Growth of second stage mineral in Lytechinus variegatus. (4th July 2018) - Stock, S. R.; Seto, Jong; Deymier, A. C.; Rack, A.; Veis, A.
ABSTRACT: Purpose and Aims : Sea urchin teeth consist of calcite and form in two stages with different magnesium contents. The first stage structures of independently formed plates and needle-prisms define the shape of the tooth, and the columns of the second stage mineral cements the first stage structures together and control the fracture behavior of the mature tooth. This study investigates the nucleation and growth of the second stage mineral. Materials and Methods : Scanning electron microscopy (SEM) and synchrotron microComputed Tomography characterized the structures of the second phase material found in developing of Lytechinus variegatus teeth. Results : Although the column development is a continuous process, defining four phases of column formation captures the changes that occur in teeth of L. variegatus . The earliest phase consists of small 1–2 µm diameter hemispheres, and the second of 5–10 µm diameter, mound-like structures with a nodular surface, develops from the hemispheres. The mounds eventually bridge the syncytium between adjacent plates and form hyperboloid structures (phase three) that appear like mesas when plates separate during the fracture. The mesa diameter increases with time until the column diameter is significantly larger than its height, defining the fourth phase of column development. Energy dispersive x-ray spectroscopy confirms that the columns contain more magnesium than the underlying plates; the ratios of magnesium to calcium are consistent with compositions derived from x-ray diffraction. Conclusion : Columns grow from both bounding plates. The presence of first phase columns interspersed among third stage mesas indicates very localized control of mineralization.